PELATIHAN PEMBUATAN MINIPRINT DENGAN MENGGUNAKAN MEDIA TRIPLEK DI KOMUNITAS MAKMOER ART PROJECT SUKOHARJO - sigit purnomo adi (Institut Seni Indonesia Surakarta, 2021)
Abstract Miniprint is one of the print size formats in graphic arts that is not yet very popular in Indonesia. Miniprint format prints in small sizes both matrix and paper. Printing in small sizes is fun. Small format requires patience and technical skill in visualizing the artist's ideas and ideas. Considering that miniprints have many features apart from a small format, they can also be carried everywhere and can also be used as an aesthetic element or room decorator and have good selling power, encouraging the author to hold a workshop or training on making miniprints in the Makmoer Art Project Sukoharjo community. The selection of the training venue in the Makmoer Art Project Community is because this community is indeed engaged in the arts and humanity. A community that always provides free workshops to people in need. Community service methods, problem identification, training and mentoring, evaluation. The works produced in this training after completion are then framed in a minimalist way. The miniprints produced are small-sized works of graphic art, using a matrix of plywood. These works are used as aesthetic elements of the house or as room decoration. Works for the aesthetic element of the house are currently popular among the public so that they have a selling value and can be used as an alternative in entrepreneurship.